Dinamika Collaborative Governance pada Destinasi Berbasis Komunitas : Studi Kasus Kawasan Dermaga Kereng Bangkirai - Danubarti, Enjelie Cepianty; Setiani, Alicia Dhela; Esterlin, Stevani (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2026)
Current tourism development emphasizes a collaborative governance approach as an effort to realize sustainable and community-based destination management. The Kereng Bangkirai Pier area is a local destination in Central Kalimantan that has developed through collaboration involving the Tourism Office, local communities, the Tourism Awareness Group (Pokdarwis), and tourism businesses. This study aims to analyze the dynamics of collaborative governance in community-based tourism destination management in the Kereng Bangkirai area. This study uses a qualitative approach through data collection techniques using literature study and documentation methods through direct observation at tourist sites. The results show that collaborative governance is formed through interactions between actors. However, in practice, it still faces challenges in the form of suboptimal coordination and uneven community participation. This study emphasizes the importance of strengthening collaboration mechanisms to support the sustainability of tourism management in the Kereng Bangkirai Pier area.